2010
DOI: 10.1590/s1519-69842010000400009
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton assemblages in a reservoir cascade of a large tropical - subtropical river (SE, Brazil)

Abstract: The phytoplankton assemblages from eight reservoirs of the Paranapanema River were studied during two consecutive years. Chlorophyceae and Bacillaryophyceae dominated in richness. The observed high number of taxa, 234, reflects the extensive sampling programme and evidences the necessity of considering the whole hydrograph basin to assess the biodiversity status of inland water ecosystems. The dams had a negative effect on phytoplankton richness, with higher number of taxa associate to riverine (non-regulated)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
64
3
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 31 publications
8
64
3
9
Order By: Relevance
“…Compared to other studies in the La Plata basin (e.g., PAGGI & JOSÉ DE PAGGI 1990, LANSAC-TOHA et al 2002, SILVA & MATSUMURA-TUNDISI 2002, NOGUEIRA et al 2008, the number of species found in this study is considerably high, and this was After 20 attempts we found two convergent solutions for NMDS. This analysis (Fig.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Compared to other studies in the La Plata basin (e.g., PAGGI & JOSÉ DE PAGGI 1990, LANSAC-TOHA et al 2002, SILVA & MATSUMURA-TUNDISI 2002, NOGUEIRA et al 2008, the number of species found in this study is considerably high, and this was After 20 attempts we found two convergent solutions for NMDS. This analysis (Fig.…”
Section: Discussioncontrasting
confidence: 66%
“…Lower richness of cyclopoid species tends to be found in limnetic waters, where generally few abundant species dominate. Clear tendencies in some ecological attributes can be observed for copepods and other crustaceans in reservoirs (SILVA & MATSUMURA-TUNDISI 2002, NOGUEIRA et al 2008.…”
mentioning
confidence: 93%
“…Borges et al (2010), in experiment with tilapia (Oreochromis niloticus L.) in net cages in an arm of Rosana reservoir, observed an increase in the concentration of total nitrogen and ammonium after the installation of the net cages, and also found strong influence of the reservoir hydrodynamics on the cultivation system. Indeed, the hydrodynamic has been pointed out by several authors (Diaz et al, 2001;Silva et al 2005;Araripe et al, 2006;Alves and Baccarin, 2007;Nogueira et al 2010) as driving the changes to the abiotic variables. Thus, the fish cultivation can cause eutrophication of the system, especially in environments with low time of water renewal (Araripe et al, 2006).…”
Section: Discussionmentioning
confidence: 95%
“…hydrodynamics and trophic state) (e.g. Rosén, 1981;Sommer, 1984;Vincent and Dryden, 1989;Reynolds, 1992Reynolds, , 1999Padisák et al, 1999;Nogueira et al, 2010). The structure of algae assemblages (e.g.…”
Section: Introductionmentioning
confidence: 99%